Analysis of Peanut Using Near-Infrared Spectroscopy and Gas Chromatography–Mass Spectrometry: Correlation of Chemical Components and Volatile Compounds. Issue 3 (3rd March 2016) - Lin, Mao; Long, Mingxiu; Li, Guolin; Chen, Xi; Zheng, Jiong; Li, Chao; Kan, Jianquan
Abstract : Peanut contains protein, oil, oleic acid, and linoleic acid its flavor is largely determined by pyrazine and aldehyde compounds. Both nutritional value and flavor are standards for measuring peanut quality. In this report, the contents of protein, oil, oleic acid, and linoleic acid were determined using near-infrared reflectance spectroscopy, and flavor compounds were identified using headspace solid-phase microextraction combined with gas chromatography–mass spectrometry in 12 different peanut cultivars. Our results showed that the content of oleic acid in raw peanut ranged from 35.69 to 82.79 g/100 g oil and the linoleic acid content ranged from 2.92 to 44.19 g/100 g oil, with high coefficients of variation. The coefficients of variation of protein and oil were lower, with content of 26.97–33.07 g/100 g raw materials and 45.53–55.53 g/100 g raw materials, respectively. Overall, 14 volatile components were isolated and identified, among which pyrazine and aldehyde compounds were the major aroma components in 12 different peanut cultivars.. Based on these results, peanuts with high protein content have high linoleic oil levels but low oleic oil levels, and roasted peanuts have a high content of pyrazines but low content of aldehydes. The results of this study will enable manufacturers to develop simple tests that predict the flavor of roasted peanuts based on their composition.